MEMBANGUN JARINGAN VIRTUAL PRIVATE NETWORK (VPN) DENGAN METODE TUNNELING MENGGUNAKAN MIKROTIK UNTUK KOMUNIKASI LOKAL DI STMIK PPKIA PRADNYA PARAMITA MALANG - Habibi, Ahmad; Arifin, Samsul (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
MikroTik RouterOS â¢ is the operating system and which can be used to make the computer even become a reliable network routers , includes a comprehensive range of features for network and wireless , one of the reliable features is a VPN ( Virtual Private Network ) .VPN ( Virtual Private Network ) is a way to create a network is " ptivate " and safe to use a public network , such as the Internet . In the world of computer networks known term tunnel , often called a tunneling technique . This technique allows a local network ( private ) associated with other local network , through a public network ( Internet ) . The data to be sent from one local network to another local network will be in the pack ( encapsulation ) by other protocols. Keywords : MikroTik, VPN (Virtual Private Network), Tunneling.